Coreferential Devices in the Quranic Interpretation - Muhassin, Mohammad; Hidayati, Dewi Ayu (Universitas Islam Negeri Raden Intan Lampung, 2019)
This article mainly discusses the coreference in the Quranic interpretation of Surah Albaqarah by Abdullah Yusuf Ali. The aims of the research are: to describe and explain the coreference types found in the Quranic interpretation, the coreference devices, and relationship types of the coreferential devices. The is a kind of descriptive qualitative research. The population consisted 286 interpretation texts of Surah Al-Baqarah with 112 samples taken as the data of the research chosen by using purposive sampling technique. The result of the research shows that the coreference types found in the Quranic interpretation are: repetition (6,55%), lexical change (18,03%), substitution (50,81%) and ellipsis (24,59%). Meanwhile, the coreferential devices found are: repetition, lexical change, and substitution. Finally, the relationship types of the co-referential devices are anaphoric (88,52%) and cataphoric (11,48%)